How (Not) to Commemorate Cicero: Asinius Pollio in Seneca’s Sixth Suasoria - Pieper, Christoph (Histos, 2019)
The article examines the three references to Asinius Pollio in Seneca the Elder’s sixth Suasoria. It reads them as an authorial meta-reflection about the interplay between cultural memory and literary or rhetorical emulation. While attempting to canonise Cicero as a cultural and political icon, Seneca invites his readers to participate in this canonisation by imitating both Cicero’s own works and earlier declaimers and historians who have written about him. Asinius Pollio is a key figure for this programme in the Suasoria, in that he does not participate in this game and therefore acts as a negative exemplar for Seneca’s readers.